Image quality and radiation dose in 256-slice cardiac computed tomography: Comparison of prospective versus retrospective image acquisition protocols - Hosch, Waldemar P.; Heye, Tobias; Schulz, Felix; Lehrke, Stephanie; Schlieter, Martin; Giannitsis, Evangelos; Kauczor, Hans-Ulrich; Katus, Hugo; Korosoglou, Grigorios (European journal of radiology, 2011)
Purpose - To assess coronary artery image quality and patient radiation exposure in patients who underwent clinically indicated 256-slice CTA. - Methods - Consecutive patients (n=193) underwent 256-slice CTA, using (1) retrospective gating without radiation dose modulation, (2) retrospective gating with radiation dose modulation and (3) prospective gating. Image quality was determined by consensus of two experienced observers using a 5-grade scale. The effective dose was calculated. - Results - In all patients, CTA was performed without adverse events. Retrospective CTA was assessed in 39 patients with and 39 without dose modulation, while 115 patients underwent prospective CTA. Heart rate was related to image quality with all protocols (r=0.46, p<0.001). Up to a heart rate of 75bpm no significant difference in overall image quality was observed for all three protocols, while no significant differences could be observed between retrospective CTA with and without dose modulation for any segments or heart rates. Prospective and retrospective CTA with dose modulation showed radiation savings of ∼75% and ∼30%, respectively compared to retrospective CTA without dose modulation (p<0.001). - Conclusions - In patients with heart rates up to 75bpm prospective CTA should be the first choice acquisition protocol. For heart rates >75bpm, retrospective CTA with dose modulation should be considered.
Available online 13 August 2010
Gesehen am 30.06.2022